2021
DOI: 10.3390/f12060779
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Science Data to Measure Human Use of Green Areas and Forests in European Cities

Abstract: Understanding and explaining the use of green spaces and forests is challenging for sustainable urban planning. In recent years there has been increasing demand for novel approaches to investigate urban green infrastructure by capitalizing on large databases from existing citizen science tools. In this study, we analyzed iNaturalist data to perform an assessment of the intentional use of these urban spaces for their value and to understand the main drivers. We retrieved the total number of observations obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Our results show that citizen science participants in our study area tend to use the area's trail network differently than other visitors, so their needs may be overlooked if not explicitly considered. Citizen science participants may even serve as a useful proxy to represent a broader group of nature‐oriented visitors whose area use might differ in similar ways from the more activity‐oriented visitors captured in the Strava Metro data (Cambria et al., 2021; Havinga et al., 2020). The Strava Metro dataset is itself biased toward visitors with a focus on athletic recreation, though a recent study elsewhere in Norway found a high correlation between Strava activities and absolute counts of segment users, suggesting that Strava is relatively representative of the dominant trends in segment use, particularly in areas of high activity (Venter et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that citizen science participants in our study area tend to use the area's trail network differently than other visitors, so their needs may be overlooked if not explicitly considered. Citizen science participants may even serve as a useful proxy to represent a broader group of nature‐oriented visitors whose area use might differ in similar ways from the more activity‐oriented visitors captured in the Strava Metro data (Cambria et al., 2021; Havinga et al., 2020). The Strava Metro dataset is itself biased toward visitors with a focus on athletic recreation, though a recent study elsewhere in Norway found a high correlation between Strava activities and absolute counts of segment users, suggesting that Strava is relatively representative of the dominant trends in segment use, particularly in areas of high activity (Venter et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that citizen science participants in our study area tend to use the area's trail network differently than other visitors, so their needs may be overlooked if not explicitly considered. Citizen science participants may even serve as a useful proxy to represent a broader group of natureoriented visitors whose area use might differ in similar ways from the more activity-oriented visitors captured in the Strava Metro data (Havinga et al 2020, Cambria et al 2021). The Strava Metro dataset is itself biased towards visitors with a focus on athletic recreation, though a recent study elsewhere in Norway found a high correlation between Strava activities and absolute counts of segment users, suggesting that Strava is relatively representative of the dominant trends in segment use, particularly in areas of high activity (Venter et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…From the economical point of view, most of the mowing activities are carried out by external procurements (90.2%), followed by internal gardener's staff (7.6%), sponsorships (1.1%), and collaboration agreements (1.1%). The distribution of participation [65][66][67][68] within the study area and a user-oriented management approach to support social inclusion (sponsorships and collaboration agreements) is represented in Figure 9.…”
Section: Management Approach For Uos's Maintenancementioning
confidence: 99%
“…At the European level, 70% of mowing is disposed of and 30% is recovered [66,67]. In Italy, the products resulting from the maintenance of public green areas are approximately 1.9 × 10 6 t/y, more than 27% of the produced organic waste [22].…”
Section: Mowing and Pruningmentioning
confidence: 99%